2011
DOI: 10.1177/1053451211406546
|View full text |Cite
|
Sign up to set email alerts
|

Creating Safe Environments for Students With Disabilities Who Identify as Lesbian, Gay, Bisexual, or Transgender

Abstract: Adolescence is an important time in human development. Teenagers spend much time questioning their core belief structures and developing the foundations of their identity. For students who identify as lesbian, gay, bisexual, or transgender (LGBT), this path of development is difficult in American schools because of strongly held homophobic beliefs. Barriers in sexuality identity development could cause problems for students with disabilities, including low self-esteem, psychological problems, and suicidal idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…youth are frequently considered a population at risk (Morgan, Mancl, Kaffar, & Ferreira, 2011). Though LGBTQ adolescents are not a homogenous population and do not experience all risks identically, these youth generally tend to have poorer emotional, psychological, behavioural, and educational outcomes than their non-LGBTQ peers (Fisher et al, 2008;Robinson & Espelage, 2011).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…youth are frequently considered a population at risk (Morgan, Mancl, Kaffar, & Ferreira, 2011). Though LGBTQ adolescents are not a homogenous population and do not experience all risks identically, these youth generally tend to have poorer emotional, psychological, behavioural, and educational outcomes than their non-LGBTQ peers (Fisher et al, 2008;Robinson & Espelage, 2011).…”
mentioning
confidence: 99%
“…This population's particularly high risk of suicidality in both the United States and Canada (Dyck, 2012) has led to research suggesting suicide is the "the leading cause of death among LGBTQ adolescents" (Fisher et al, 2008, p. 80), with some estimates indicating up to 40% of these youth have made a suicide attempt. Suicidality "refers to the occurrence of suicidal thoughts or suicidal behavior" (Galaif, Sussman, Newcomb, & Locke, 2007, p. 27) and incorporates both cognitions and actions Elevated LGTBQ youth suicidality has been linked to high rates of violence, discrimination, and identity-based bullying (Berlan, Corliss, Field, Goodman, & Austin, 2010;Fisher et al, 2008;Morgan et al, 2011), as well as low levels of social support (Detrie & Lease, 2007). For example, LGBTQ adolescents frequently experience verbal (80%) or physical harassment (25 to 40%) or violence (20%) related to their sexuality and/or gender expression (Morgan et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the term "homophobia" was used in 58 products belonging to the field of disability study. Among them, 5 are books and book chapters (HALDEMAN, 2001;MAIL and LEAR, 2006;MCRUER, 2006a, b;TREMAIN, 1996), 52 are journal papers (ABBOTT and HOWARTH, 2007;BAROUNIS, 2009;BLYTH and CARSON, 2007;BURNS and DAVIES, 2011;CAMBRIDGE, 1999;CORKER, 2001;DUKE, 2011;ELMAN, 2012;ERICKSON, 2007;FRALEY, MONA, and THEODORE, 2007;GRIEVE et al, 2009;GROSSMAN, D'AUGELLI, and DRAGOWSKI, 2007;HAMILTON, 2009;HANJORGIRIS, RATH, and O'NEILL, 2004;HASH and NETTING, 2009;HELLMAN and KLEIN, 2004;HENRY, FUERTH, and FIGLIOZZI, 2010;HIGGINS, 2010;HINGSBURGER and TOUGH, 2002;HINRICHS et al, 2010;HUNT et al, 2006;JOHNSON et al, 2005;KAFER, 2003;LANGLEY, 2001;LEBLANC et al, 2001;LIPTON, 2004;LUCKSTED, 2004;MCCLELLAND et al, 2012;MORGAN et al, 2011;O'TOOLE, Corbett J. and BROWN, 2002;O'TOOLE, Corbett Joan and DOE, 2002;PARKES, 2006;PEATE, 2008;PERLIN, Michael L, 2013;PERLIN, Michael L., 2011;ROBERTSON, 2003;SHAKESPEARE, 1999a, b;…”
Section: Resultsmentioning
confidence: 99%
“…When people have more than one stigma, due to their belonging to more than one minority group, as in the case of LGBT people with disability, they are part of a minority within a minority (BENNETT and COYLE, 2007). In this particular condition the threats they face substantially increase, compromising their self-esteem and psychological well-being (BENNETT et al, 2007;HIGGINS, 2010;MORGAN et al, 2011;SHAKESPEARE, 1999a). One of the most important barriers that LGBT disabled people have to deal with is the homophobic beliefs of their relatives and caregivers (HINRICHS and VACHA-HAASE, 2010;LEBLANC and TULLY, 2001).…”
Section: Introductionmentioning
confidence: 99%